2-(1-Methyl-2-oxoindolin-3-ylidene)malononitrile - Wang, De-Cai (International Union of Crystallography, 2013)
The title molecule, C(12)H(7)N(3)O, is almost planar, with an r.m.s. deviation of 0.026 Å. No directional interactions could be detected in the crystal.